A closer look at politically connected corporations: evidence from Citizens United. Issue 5 (4th April 2019) - Newton, Ashley N.; Uysal, Vahap B.
Abstract : Purpose: The purpose of this paper is to examine the effects of political connections surrounding an exogenous Supreme Court decision (Citizens United) that lifted long-standing restrictions on corporate political contributions. Design/methodology/approach: This study examines key characteristics of politically connected firms compared to non-politically connected firms, including their market reaction to Citizens United, as well as cash holdings levels and governance characteristics before vs after the landmark decision. Findings: The results indicate a significant negative market reaction to politically connected firms surrounding the announcement of Citizens United. Additionally, there is a significant increase in the cash holdings of politically connected firms relative to before the event and relative to non-politically connected firms. For politically connected firms, this result is exacerbated by poor corporate governance quality. Collectively, these findings are consistent with a positive association between agency costs and political connections. Originality/value: This study provides novel evidence by exploiting an exogenous enhancement in the implications of political connections that accompanied the Citizens United decision. The use of this quasi-natural experiment offers an ideal research setting to extract fresh insights into the effects of corporate political connections.